Environmental Risk Factors that Influence Malaria Incidence: Literature Review - Ayda Fitri Madani; Eva Triani; Nurmi Hasbi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Malaria is an infectious disease that continues to pose a global health threat. Malaria cases will reach 247 million in 2021, with malaria accounting for an estimated 619,000 fatalities worldwide. Indonesia is the second largest provider of malaria cases in the WHO South-East Asia Region, trailing only India. In 2020, Indonesia contributed 254,050 positive cases of malaria. In 2021, the number of cases has risen to 304,607. Objective: The goal of this research is to determine the factors of the physical condition of the house (including the use of wire mesh for ventilation, the presence of ceilings, and the density of walls) and the environment around the house (including the presence of bushes, puddles of water, and livestock pens) that influence the incidence of malaria. Method: This research is a literature review that use the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) technique. The literature search was carried out on the internet using Google Scholar. Out of the search results, 11 articles were chosen for review. Results: The results of this study indicate that the use of wire mesh for ventilation, the presence of ceilings, the density of walls, the presence of bushes, the presence of standing water, and the presence of livestock pens in the environment surrounding the house are risk factors that influence the incidence of malaria. Conclusion: The physical condition of the house and the quality of the surrounding environment are both important factors to consider in malaria prevention measures.